(untitled) (Fiep Bulletin - online, 2014)
The Breast Cancer is a disease who exceeds the exclusive interest of the medical areas, becouse the women consider, the symbol biggest of its feminilidade, the breast. The cancer is the uncontrolled growth of cells derived from normal fabrics being capable to kill its host for the dissemination of the cells, since the origin place until distant places. The potential of growth of the Breast Cancer and the resistance of the patient to the malignant neoplasia vary with the individual. The advanced phase of the cancer reaches in low-level economic and educational women. We can’t to prevent the appearance it mammary tumor, only if the precocious diagnosis has as resource as preventive form, and in such a way, to preserve the woman, and your mutilation or the death. In view of that the woman must be informed and apt to develop practical preventive being helped it to recognize it the illness in initial phases, considered to investigate in this work, the influence of the degree of instruction in the practical one of the precocious diagnosis. Parallel, we observe the behavior of the women with regard to the frequency of accomplishment, the first source of the information and the practical one of the precocious diagnosis. Women of 35 the 60 years had been invited to answer a questionnaire, being formed groups with low and high instruction of degree. She was observed that both groups consults the gynecologist annually and this is the first source of the precocious diagnosis. The group with bigger degree of instruction realize less practises of the precocious diagnosis than group with low degree of instruction. We conclude that the women with low degree of instruction have greater attention to the precocious diagnosis, probably for the biggest difficulty of the access to the medical treatment.